Labial Frenectomy with Conventional Scalpel Technique as Preliminary Preparation for Diastema Closure: A Case Report - Annisa Anindya; Cherryl Sania Mahira; M. Yusuf Diansyah (SONDE (Sound of Dentistry), 2025)
Introduction: Midline diastema refers to a space between the maxillary central incisors, commonly observed in children and typically resolving with age. However, approximately 6% of cases persist into adolescence or adulthood, potentially compromising smile aesthetics. One etiological factor in such persistent cases is an abnormally wide or elongated maxillary labial frenum extending between the central incisors. Surgical management via frenectomy is often indicated. The aim of this case report is to highlights the management of a papillary penetrating frenum type using conventional frenectomy. Case report: A 16-year-old female patient reported dissatisfaction with the appearance of her smile due to a noticeable gap in the maxillary anterior region. Intraoral examination revealed a high attachment of the maxillary labial frenum accompanied by a midline diastema. The patient was diagnosed with a mucogingival deformity in the form of a high maxillary labial frenum attachment, classified as the papillary penetrating type. The chosen treatment was a conventional frenectomy using a single hemostat technique. Postoperative follow-up demonstrated a transition of the frenal attachment to the gingival type, thereby facilitating the initiation of fixed orthodontic therapy to correct the diastema. The frenectomy procedure resulted in favorable outcomes without any complications. Discussion: Conventional scalpel frenectomy using a single hemostat technique may be an option as a first step before orthodontic treatment. The procedure effectively repositioned the frenum attachment and created favorable conditions for preliminary preparation. Conclusion: Conventional frenectomy using the single hemostat technique proved to be an effective and safe treatment for high maxillary labial frenum attachment. Keywords: Frenectomy, Maxillary labial frenum, Midline diastema